Class II members of the poly(A) binding protein family exhibit distinct functions during Arabidopsis growth and development. Issue 1 (2nd January 2017) - Gallie, Daniel R.
ABSTRACT: The poly(A)-binding protein (PABP) binds to the poly(A) tail of eukaryotic cellular mRNAs and contributes to their stability and translational efficiency. In plants, PABP is expressed from an unusually large gene family grouped into 3 classes that expanded during the evolution of land plants. Subsequent to expansion of the family, members diverged in their primary sequence and in expression. Further expansion of the family and divergence of its members in the Brassicaceae demonstrate the continued dynamic evolution of PABP in plants. In this study, the function of the widely-expressed class II PABP family members was examined to determine how individual class II members contribute to plant growth and development. Of the 3 class II PABP members, PAB2 and PAB4 contribute most to vegetative growth and vegetative-to-floral transition whereas PAB2, and the recently-evolved third class II member, PAB8, contribute to inflorescence and silique growth. Interestingly, although class I and class III PABP members are expressed specifically in reproductive organs, class II PABP members are also necessary for fertility in that the combinatorial loss of PAB2 and either PAB4 or PAB8 expression resulted in reduced fertility. Although all 3 class II members are required for protein expression, PAB4 contributes most to the steady-state level of a reporter mRNA and to protein expression. These findings suggest that class II PABP members are partially overlapping in function but also involved in distinct aspects of plant growth and development.